TOWARDS A BETTER POLICY FOR AIRLINE PASSENGERS WITH REDUCED MOBILITY - Konstantinos MALAGAS; Ridha Aditya NUGRAHA; Sofoklis ALEPIS; Nikitas NIKITAKOS; Rio CHRISTIAWAN; Vicia SACHARISSA (Scientific Journal of Silesian University of Technology. Series Transport)
Persons with reduced mobility (PRM) should enjoy the same rights as other people in all life aspects, including in terms of travel experience. PRM group is an undeveloped travel market segment, having specific needs that the aviation organizations should satisfy. The facilitation of air travel for PRM should be supported by, among others, clear standards and appropriate regulations and laws. The present study focuses on the European Union (EU) and ASEAN regulatory framework for PRM, presenting various issues and suggesting improvements. The paper is theoretical in nature. It compares various regulations and laws that are implemented in the two Regions, and from thereafter suggestions are generated. The study shows that the European Union has a more efficient regulatory framework that better responds to the transportation chain and the needs of the various groups of PRM. The ASEAN Region can adopt some functional regulations and practices from the European Region. Also, the emphasis should be moved from persons with disabilities to PRM accompanied by the necessary rules, mainly from the ASEAN side. PRM makes up a significant potential market segment in aviation and relevant studies will be beneficial. The study provides significant insights for the aviation industry, particularly for these two Regions, the various groups of PRM, and the policymakers.